Analisis Determinan Fungsi Intermediasi dan Profitabilitas Bank Umum Syariah di Indonesia - Harry Satria Suardin; Lukman Hakim; Novi Mubyarto (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2022)
This study aims to identify and analyze the direct effect of third party funds (DPK), capital adequacy (CAR), and problem finance (NPF) on the intermediation function (FDR) of sharia commercial banks in indonesia. The sampling technique used is purposive sampling, the number of samples obtained from all Islamic commercial banks in Indonesia for the period January 2013-February 2021. The data were analyzed by path analysis using the PLS method assisted by the SPSS program. The results showed that Third-Party Funds (TPF), Capital Adequacy Ratio (CAR), and Non-Performing Financing (NPF) had a significant direct negative effect on the intermediation function (FDR). Furthermore, for the profitability variable, the results of the study show that the Capital Adequacy Ratio (CAR) and Non Performing Financing (NPF) directly have a significant negative effect on Profitability (ROA). However, Third-Party Funds and Intermediation Functions have no direct significant effect on profitability. For the mediator variable, the results show that the intermediation function has not been able to mediate the independent variables of Third-Party Funds (TPF), Capital Adequacy Ratio (CAR), and Non Performing Financing (NPF) on Profitability (ROA).